قراءة تحليلية في خصائص النص القرآني ومزاياه: An analytical study of the characteristics and advantages of text of the Quran - Tahhan, Mohammed Abdulraheem; Abdo Khaled, Nashwan (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2023)
ملخص البحث القرآن الكريم آخر الكتب الإلهية وأشملها، وجاء لإصلاح شؤون الخلق أجمعين إلى قيام الساعة، وامتاز نصه بخصائص لم تتوافر في أي من الكتب السماوية قبله، ولا في الكتب الوضعية البشرية قبله وبعده، وذُكرت مزايا متفرقة للنص القرآني ومتعددة من قبل علماء المسلمين والباحثين، وقد جمعت هذه الدراسة المزايا بشكل جامع موجز شامل لجميع ما قيل في مزايا النص القرآني الكريم، فاللنص القرآني العظيم خصائص كثيرة، كل منها محكم كريم، ينفرد بها ويتميز عما عداها من نصوص المخلوقين، وأجملتها في إحدى عشرة مزية، يتميز بها عن غيره وينفرد بها وهي: خالد محفوظ مصون، مقدس ميمون، محكم في مبناه يهدي للتي أقوم في معناه، وسط، يزكي العقل، ويغذي الفطرة، عالمي جنسية أهله فوق الجنسيات، شامل لجميع جوانب الحياة، ويتسع لما كان، وماهو كائن، وما سيكون، يرتبط بالأصل ومتصل بالعصر، يصدع بالحق ولا يبالي بأحد من الخلق، أسلوبه فريد أخاذ يأخذ بمجامع القلوب والألباب، حاز أعلا رتب الشرف والكمال والأفضلية في مصدره، ومبلغه، وحملته، والميزة الأخيرة العجيبة والتي ليس لها مثيل أن جمعه ونقله يدهش العقول حيرة، ويزيد القلوب يقيناً وطمأنينة. ABSTRACT The Holy Qur'an is the final and most comprehensive of the divine books, and it came to settle the affairs of the worlds until the Day of Judgment. Its text was distinguished by features that were not present in any of the heavenly books that came before it, nor in any of the human-made books that came before and after it. The magnificent Qur'anic book has numerous features, each of which is exact and generous, unique to it and distinguishable from other texts of creatures, and I have summed them up in eleven absolute advantages, even though their number exceeds a hundred. It is distinguished from others and is unique to it, and it is permanent, preserved, holy, and auspicious, airtight in its structure, guiding to what is most upright in its meaning, middle, purifying the mind, and nourishing the instinct, cosmopolitan of the nationalities of its people above nationalities, inclusive of all aspects of life, and accommodates what was and what is, and what will be, It is related to the origin and connected to the modern era, it pronounces the truth and does not care about anyone from the creation, its style is unique and captivating, it captures the gatherings of hearts and minds, it has the highest ranks of honor, perfection and preference in its source, its reach, and its carrier, and the last amazing feature that has no equal is that its collection and transmission amazes minds with confusion, and increases hearts certainly and reassuringly.